Anywhere you go - Morrissey, Bridget (Berkley Romance, 2025)
"Tatum Ward and Eleanor Chapman lead totally opposite lives. Tatum's never left her Midwestern hometown. She resides in a quaint guest cottage on her parents' property while working part-time as a waitress, where she spends most shifts ignoring her feelings for a beautiful regular named June. Eleanor dedicates every waking hour to her high-profile press career, sacrificing personal relationships for professional success, save for the occasional hookup to fight off her loneliness. When both women's lives unexpectedly blow up at the exact same time, they each need an escape, and fast. In Tatum's hometown, Eleanor expects a quiet hideaway where she can recharge. Instead she gets wrapped up in the family drama that Tatum left town to avoid, pulled in by Tatum's charismatic older sibling, Carson, who charms Eleanor at every turn. Tatum ends up in Eleanor's New York high-rise apartment with June. One week together in the big city might make it impossible for Tatum to avoid not just her true feelings for June, but her real dreams for her life. Amid a friendship with a reclusive Hollywood actress and a complicated family reunion, Tatum and Eleanor each discover much more than they bargained for away from home. Their house swap won't last forever, but it might be just long enough for both women to surrender their defenses and finally fight for the life-and love-they deserve"--